Identification of the vascular endothelial growth factor signalling pathway by quantitative proteomic analysis of rat condylar cartilage - Jiang, Liting (FEBS Open Bio, 2016)
Angiogenesis mediated by vascular endothelial growth factor (VEGF) is known to play an important role in regulating cartilage remodelling and endochondral ossification. However, the details of how VEGF signalling mechanisms affect condyle remodelling in response to alterations in functional loading remains unclear. To explore this, eighty 16‐day‐old male SD rats were divided into two equal groups which were fed either a soft/powdery diet or a hard diet for 4 weeks; the stiffness of the diet results in alteration of mastication force and hence temporomandibular joint (TMJ) development. We performed a proteomic analysis of rat condylar cartilage using isobaric tags for relative and absolute quantification (iTRAQ) labelling, followed by 2D nano‐high performance liquid chromatography and MALDI‐TOF/time‐of‐flight technology. After protein identification, we used biological information analysis to identify the differentially expressed proteins associated with the VEGF signalling pathway. Among the identified differentially expressed proteins, we found VEGF signalling mainly via the p44/42 MAPK and p38 mitogen‐activated protein kinase (MAPK) pathways in condylar cartilage, including VEGFD, VGFR2, KPCB, KPCT, KPCZ, ARAF, RASN, PLCG2, PLCG1, JUN and M3K12. Furthermore, four representative protein candidates, VEGF, p38 MAPK and p44/42 MAPK/phospho‐p44/42 MAPK, were confirmed by immunohistochemical staining and western blot. Our data suggest that VEGF might play an important role in TMJ development and remodelling in response to alterations in functional loading through the p44/42 MAPK and p38 MAPK signalling pathway. This study provides new clues to the understanding of the signalling mechanism responsible for VEGF production in response to different masticatory functions at the protein level.